FRI0349 Associations Between Serum Biomarkers of and Lifestyle Risk Factors for Inflammatory Arthritis in First Degree Relatives of Patients with Rheumatoid Arthritis: Results from the Pre-Clinical Evaluation of Novel Targets in RA (PREVENT RA) Study. (9th June 2015) - Sergeant, J.C.
Abstract : Background: Rheumatoid factor (RF), anti-cyclic citrullinated peptide antibodies (anti-CCP) and C-reactive protein (CRP) are known serum biomarkers of inflammatory arthritis (IA). They have a potential role in the prediction of incident rheumatoid arthritis (RA), particularly in high risk groups such as participants in the PRe-clinical EValuation of Novel Targets in RA (PREVeNT RA) study, a register of first degree relatives (FDRs) of patients with RA. Objectives: To assess the associations of RF, anti-CCP and CRP levels with lifestyle risk factors for IA from an established risk score [1]. Methods: FDRs of patients with established RA are being recruited from across the United Kingdom. FDRs are free of IA and >30 years old at time of recruitment. Following informed consent, participants complete an online questionnaire to ascertain lifestyle factors potentially associated with risk of RA and provide a blood sample for central storage and analysis. For this study, we measured RF (normal ≤20 IU/ml), anti-CCP (normal ≤7 U/ml) and high sensitivity (hs) CRP (normal ≤5 mg/l) on FDRs recruited up to November 2014. Associations between these biomarkers and current smoking status, alcohol intake (units/week), body mass index (BMI, kg/m 2 – derived from self-reported height and weight) and self-reported diabetes were assessed with Fisher's exact or Mann-Whitney tests, then adjusted for age and sex with multiple logistic or linear regression. Results: Complete serum biomarker and lifestyle risk factor data were available for 293 participants: 220 (75%) were female, median age at recruitment was 51 (IQR 41-62) years. 14 participants (4%) were RF positive, 4 (1%) were anti-CCP positive and 56 (19%) had an elevated hsCRP. 20 (7%) were current smokers, 10 (3%) reported being diabetic, median alcohol intake was 5 units/week (IQR 1-12) and median BMI was 25.3 kg/m 2 (IQR 22.4-28.7), with 61 (21%) obese (BMI ≥30 kg/m 2 ). RF positive participants were more likely to be current smokers (p=0.01; adjusted OR 6.21, 95% CI (1.72, 22.43)). Elevated CRP was associated with higher BMI (p<0.001), with a difference in adjusted means of 3.85 kg/m 2 (95% CI (2.40, 5.30)), and subjects with an elevated CRP were also more likely to report being diabetic (p=0.004; adjusted OR 6.15, 95% CI (1.63, 23.21)). We found no association between these serological markers and alcohol consumption. Conclusions: In this FDR cohort several lifestyle factors associated with future onset of IA were also associated with biomarkers of serological risk and low-grade inflammation. These initial results suggest that early targeting of "at risk" lifestyle factors may, at a population level, reduce future risk of RA onset. References: Lahiri et al. Ann Rheum Dis 2014; 73: 219 Disclosure of Interest: None declared